Sports and Regional Growth in Sweden - Is a successful professional sports team good for regional economic growth? - Emelie Värja (Örebro University School of Business, 2014)
This study investigates whether net inbound migration and per capita income growth of a municipality is affected when a local sports team enters or exits the premium national leagues in ice hockey or soccer in Sweden. Local governments frequently support a local professional team through direct subsidies; beneficial funding of arenas, etc., which often is motivated by alleged, positive externalities through effects on the attractiveness of the municipality as a leisure-travel destination, or place for living or doing business, which ultimately is supposed to enhance the tax base and the tax revenues of the local government. Previous literature on such effects is based on simple models estimated on a selected sample of cities and without consideration of spatial interdependencies between local areas. We carry out a simultaneous estimation of spatial paneldata models of income per capita growth and net migration rates using annual data from all Swedish municipalities from 1995-2011 (except for four municipalit that have changed borders). With this richer modeling framework we still find no evidence of a positive relationship from performance of a local team on any of these two variables.
Keywords: H71; J61; L83; 330; sports; growth; spatial econometrics; regional growth